To solve the problem it is necessary to take into account the concepts related to simple pendulum, i.e., a point mass that is suspended from a weightless string. Such a pendulum moves in a harmonic motion -the oscillations repeat regularly, and kineticenergy is transformed into potntial energy and vice versa.
In the given problem half of the period is equivalent to 1 second so the pendulum period is,
[tex]T= 2s[/tex]
From the equations describing the period of a simple pendulum you have to
[tex]T = 2\pi \sqrt{\frac{L}{g}}[/tex]
Where
g= gravity
L = Length
T = Period
Re-arrange to find L we have
[tex]L = \frac{gT^2}{4\pi^2}[/tex]
Replacing the values,
[tex]L = \frac{(9.8)(2)^2}{4\pi^2}[/tex]
[tex]L = 0.99m[/tex]
In the case of the reduction of gravity because the pendulum is in another celestial body, as the moon for example would happen that,
[tex]T = 2\pi \sqrt{\frac{L}{g/6}}[/tex]
[tex]T = 2\pi\sqrt{\frac{6L}{g}}[/tex]
[tex]T = 2\pi \sqrt{\frac{6*0.99}{9.8}}[/tex]
[tex]T = 4.89s[/tex]
In this way preserving the same length of the rope but decreasing the gravity the Period would increase considerably.